PENGARUH STRES KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION (Pada Karyawan Non Medis Rumah Sakit Islam Malang UNISMA) - Reseliani Mahrofi; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTARCT The purpose of this research is to determine the effect of work stress, motivation, and work environment on turnover intention of non-medical employees of Rumah Sakit Islam Malang UNISMA. This research type is explanatory research. The research was conducted at Rumah Sakit Islam Malang UNISMA. The sample of this research was 25% of the population, 60 of 239 employee. Data collection method used is questionnaire. The analysis used includes instrument testing, normality test, multiple regression linear analysis, classical assumption test, and hypothesis test. The results of this research indicate that work stress has an important effect on turnover intention, motivation has an important effect on turnover intention, and work environment does not have an important effect on turnover intention, and work stress, motivation, and work environment influence simultaneously on turnover intention of non-medical employees of Rumah Sakit Islam Malang UNISMA.Keywords : Work Stress, Motivation, Work Environment, Turnover Intention